Ocular Surface Ion-Channels Are Closely Related to Dry Eye: Key Research Focus on Innovative Drugs for Dry Eye - Yang, Shuo; Wu, Yaying; Wang, ChunYang; Jin, Xiuming (Frontiers in Medicine, 2022)
Abundant receptor channels, including various perceptual receptors, chloride channels, purinergic receptor channels, and water channels that exist on the ocular surface, play an important role in the pathogenesis of dry eye. Channel-targeting activators or inhibitor compounds, which have shown positive effects in in vivo and in vitro experiments, have become the focus of the dry eye drug research and development, and individual compounds have been applied in clinical experimental treatment. This review summarized various types of receptor channels on the ocular surface related to dry eye, their basic functions, and spatial distribution, and discussed basic and clinical research results of various channel receptor regulatory compounds. Therefore, further elucidating the relationship between receptor channels and dry eye will warrant research of dry eye targeted drug therapy.